Herschel-ATLAS*: Evolution of the 250 μm luminosity function out to z = 0.5 - Dye, S; Dunne, L; Eales, S; Smith, D; Amblard, A; Auld, R; Baes, M; Baldry, I; Bamford, S; Blain, A; Bonfield, D; Bremer, M; et al. (2010)
We have determined the luminosity function of 250 μm-selected galaxies detected in the ∼14 deg2 science demonstration region of the Herschel-ATLAS project out to a redshift of z = 0.5. Our findings very clearly show that the luminosity function evolves steadily out to this redshift. By selecting a sub-group of sources within a fixed luminosity interval where incompleteness effects are minimal, we have measured a smooth increase in the comoving 250 μm luminosity density out to z = 0.2 where it is 3.6 +1.4-0.9 times higher than the local value. © 2010 ESO.